2017
DOI: 10.1159/000477160
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Rhegmatogenous Retinal Detachment at Late Stage following Endogenous Bacterial Endophthalmitis

Abstract: Purpose: To report a case of rhegmatogenous retinal detachment in the late stage, despite the fact that it had previously been halted after intravitreal injection of an antimicrobial agent against endogenous bacterial endophthalmitis (EBE). Case: This study involved a 62-year-old male who had previously been diagnosed with septicemia due to liver abscess and the detection of Klebsiella pneumoniae in a culture of his liver abscess, and who underwent ophthalmic examination after his conjunctival hyperemia had fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Retinal necrosis with tangential traction of retinal membranes can lead to formation of retinal breaks and rhegmatogenous RD. Tori et al reported a rapid progression of proliferative vitreoretinopathy after endogenous bacterial endophthalmitis caused by meningitis [2,22,23]. The results of our study can verify this point of late onset RD and of necessary strict follow-ups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Retinal necrosis with tangential traction of retinal membranes can lead to formation of retinal breaks and rhegmatogenous RD. Tori et al reported a rapid progression of proliferative vitreoretinopathy after endogenous bacterial endophthalmitis caused by meningitis [2,22,23]. The results of our study can verify this point of late onset RD and of necessary strict follow-ups.…”
Section: Discussionsupporting
confidence: 78%
“…Exogenous is mostly postoperative (e.g., cataract surgery), but may also be post-traumatic or related to organisms with an ability to penetrate intact corneas. It can be classified as either culture-positive or culture-negative (sterile) [1,2]. and further stratified into an acute form (within 6 weeks after surgery) which is the most common [3] and a delayed-onset form (more than 6 weeks after surgery).…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 8 Though seldom mentioned, RD may occur as a result of membranous scar tissue formation even after the inflammation has subsided. 10 Unlike the majority of patients with primary, non-complex rhegmatogenous retinal detachment, patients who develop RD after endophthalmitis generally have a poor visual prognosis, with up to two-thirds of all patients achieving a best corrected visual acuity (BCVA) of 20/400 or less even after surgical repair. 11 …”
Section: Introductionmentioning
confidence: 99%
“…Retinal necrosis with tangential traction of retinal membranes can lead to formation of retinal breaks and rhegmatogenous RD. Tori et al reported a rapid progression of proliferative vitreoretinopathy after endogenous bacterial endophthalmitis caused by meningitis 2,19,20 . The results of our study can verify this point of late onset RD and of necessary strict follow ups.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous is mostly postoperative (e.g., cataract surgery), but may also be posttraumatic or related to organisms with an ability to penetrate intact corneas. It can be classi ed as either culture-positive or culture-negative (sterile) 1,2 . and further strati ed into an acute form (within 6 weeks after surgery) which is the most common 3 and a delayed-onset form (more than 6 weeks after surgery).…”
Section: Introductionmentioning
confidence: 99%